A323 A PERSONALIZED MEDICINE APPROACH TO THE ROLE OF RECTAL INDOMETHACIN IN PREVENTING POST -ERCP PANCREATITIS: A META- ANALYSIS OF AGGREGATE SUBGROUP DATA. (1st March 2018) - YAGHOOBI, M; Alzahrani, M A; McNabb-Baltar, J; Martel, M; Tse, F; Barkun, A N
Abstract: Background: Despite initial evidence in the literature favoring rectal indomethacin in preventing post-endoscopic retrograde cholangiopancreatography (ERCP) pancreatitis (PEP), recent studies have been controversial in supporting its universal use, in part due to varying patient selection. Aims: To identify optimal patient subgroups who might benefit the most from rectal indomethacin. Methods: Data source: A comprehensive electronic literature search was done. Study selection: Randomized controlled trials (RCTs) comparing rectal indomethacin and placebo in preventing PEP. Data extraction and Synthesis: Methodological quality was assessed by the Cochrane risk of bias tool as well as Jadad scale. Statistical heterogeneity was assessed. Several subgroup, sensitivity and individual participant data were completed based on specific risk factors or patient characteristics to characterize patient populations who benefit most from the intervention. Main outcomes and Measures: The rate of PEP. Results: A total of seven out of 336 trials published between 2007 and 2016 (n=3096) were included. The pooled proportion estimate of PEP rate was 5.6% with indomethacin and 8.7% with placebo. Random model meta-analysis showed the overall rate of pancreatitis was significantly lower with rectal indomethacin [OR=0.54(0.36–0.82), number needed to treat =19]. In subgroup analysis, the difference was not significantly different in an unselected population, but was when restricting the analysis to high-risk patients [OR: 0.42 (0.27–0.66)]. Subgroup analysis showed that administering rectal indomethacin before rather than during or after procedure significantly reduced the rate of PEP [OR:0.53(0.37–076)]. Individual participant data showed rectal indomethacin significantly prevented PEP in patients with sphincter of Oddi dysfunction (SOD) [0.47(0.28–0.77)] and those undergoing biliary sphincterotomy [OR:0.72 (0.52–0.99)], but not in those undergoing pre-cut or pancreatic sphincterotomy, or prophylactic pancreatic stent placement. Rectal indomethacin also significantly decreased the rate of moderate to severe PEP in all patients [OR: 0.47 (0.28–0.79)]. Sensitivity analysis showed that the lower quality of studies favored indomethacin. Conclusions: Rectal indomethacin significantly reduces the risk of PEP in high-risk, and more specifically SOD patients; it decreases the occurrence of moderate to severe PEP in all patients, only if given pre-procedure. Additional data are needed to assess the additional contribution of prophylactic pancreatic stent placement. Funding Agencies: None